Electronic binding energy and thermal relaxation of Li and LiNa atomic alloying clusters. Issue 19 (27th April 2016) - Bo, Maolin; Guo, Yongling; Wang, Yan; Liu, Yonghui; Peng, Cheng; Sun, Chang Q.; Huang, Yongli
Abstract : We examined the effects of atomic hetero- and under-coordination on the relaxation of the interatomic bonding and electronic binding energy of Li and LiNa cluster alloying using a combination of the bond-order-length-strength correlation and density functional theory calculations. Abstract : We examined the effects of atomic hetero- and under-coordination on the relaxation of the interatomic bonding and electronic binding energy of Li and LiNa cluster alloying using a combination of the bond-order-length-strength correlation and density functional theory calculations. We found that bond nature alteration by heterocoordination, bond relaxation by thermal excitation and atomic coordination contribute intrinsically to the core-level energy shifts with resolution of the binding energy at the atomic sites of terrace edges, facets, and bulk of the LiNa alloy nanoclusters. Our strategies may simplify the complexity of core electron binding energies in analyzing the experimental data of the irregularly coordinating atoms.